2019
DOI: 10.1257/aer.20170237
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from the Great Depression: The Farm Channel in Spring 1933

Abstract: US industrial production rose 57 percent. We show that an important source of recovery was the effect of dollar devaluation on farm prices, incomes, and consumption. Devaluation immediately raised traded crop prices, and auto sales grew more rapidly in states and counties most exposed to these price increases. The response was amplified in counties with more severe farm debt burdens. For plausible assumptions about farmers' relative MPC, the incidence of higher farm prices, and the aggregate multiplier, this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Other work focuses on the role of public debt in the context of higher inflation; see, for example, Jacobson, Leeper, and Preston (2019). Hausman, Rhode, and Wieland (2019) argue that higher inflation coming from higher traded crop prices redistributed income from lenders (nonfarm households and businesses) with a relatively low marginal propensity to consume, to debtors (farmers) with a relatively high marginal propensity to consume. Cole and Ohanian (2004) argue that the recovery from the Great Depression was weak due to New Deal cartel-type policies.…”
Section: Recoverymentioning
confidence: 99%
See 2 more Smart Citations
“…Other work focuses on the role of public debt in the context of higher inflation; see, for example, Jacobson, Leeper, and Preston (2019). Hausman, Rhode, and Wieland (2019) argue that higher inflation coming from higher traded crop prices redistributed income from lenders (nonfarm households and businesses) with a relatively low marginal propensity to consume, to debtors (farmers) with a relatively high marginal propensity to consume. Cole and Ohanian (2004) argue that the recovery from the Great Depression was weak due to New Deal cartel-type policies.…”
Section: Recoverymentioning
confidence: 99%
“…Moreover, in equilibrium we can get an expression for the overall net exports. It has been argued (e.g., Hausman, Rhode, and Wieland (2019)) that because changes in net exports made small contributions to US growth in 1933 and 1934, the devaluation could not be expansionary through a higher demand for domestic goods. In the linearized version of this model, we can get an expression between net exports and terms of trade as follows:…”
Section: A2 a Model Of The Gold Standard And Tradementioning
confidence: 99%
See 1 more Smart Citation
“…On the economic history side, many theories try to explain why March 1933 marks a turning point in economic activity in the US, reflecting the fact that several policies were implemented at that time (Romer (1992), Eggertsson (2008), Hausman, Rhode, and Wieland (2019), Jalil and Rua (2016), Jacobson, Leeper, and Preston (2019), among others). 3 Eichengreen and Sachs (1985), Campa (1990), andBernanke (1995) have shown that countries that left the gold standard recovered faster than countries that remained on gold.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that real activity recovered in 1933 is not enough by itself. There are other plausible explanations for the recovery, including extremely low nominal interest rates, resuscitation of the banking and payments system after a massive financial crisis (Hanes 2019b), and the effect of dollar devaluation in raising farmers' nominal incomes relative to their debts (Hausman, Rhode, and Wieland 2019).…”
mentioning
confidence: 99%